Prehranjevalna dinamika in pojav znotrajvrstnega kleptoparazitizma v koloniji navadne čigre Sterna hirundo na Ptujskem jezeru (SV Slovenija) - Denac, Damijan (Acrocephalus, 2004)
Feeding dynamic, choice of foraging sites and intraspecific kleptoparasitism in the Common Tern Sterna hirundo colony on a concrete power line base on Ptujreservoir (river Drava, NE SLovenia) were studied on 3 Jul 2004. A group of ornithologists performed a whole day colony observation using prepared protocols. Times, directions of arrival of terns with food and terns' behaviour were registered. On the actual observation day we counted 10 chicks,15 incubating adults and 11 fledged young in the colony. Breeding density was low, maximum 0.14 nests/m2. The highest frequency of feeding chicks was recorded early in the morning (between 5 and 6 AM). During the day their activity decreased and in the evening (from 18 to 20 PM) their feeding frequency increased again. Terns arrived to the colony mostly from the NW direction (41 %), 32% of them arrived from the SE, and 27% were observed hunting on Ptuj reservoir close to the colony. In 35% of the observations, theterns with food were attacked by conspecific kleptoparasitic terns. Attackswere performed by four terns, attacking alone or in group. Kleptoparasitic terns were either attacking others with food in the air or in the colony when terns attempted to feed their young. Attacking in the air was the mosr frequent tactic (90%). Kleptoparasitic terns were feeding their youngwith the stolen fish. None of the incubating terns were fed by their partners. This was most probably adaptation to the strong kleptoparasitic pressure. Adult birds tried to avoid attacks by delivering fish very quickly to the chicks. We presume that strong kleptoparasitism was caused by a food shortage. It is possible that kleptoparasitism was only a functional response to the temporary suboptimal hunting conditions as the water was muddy to earlier havy rains.
Keywords: Behavior, Animal; Birds; Ecosystem; Ekosistem; Feeding Behavior; Hranjenje, vedenje; navadna čigra; prehranjevanje; Ptice; Vedenje živali